Assessing the determinants of uptake and hesitancy in accessing COVID 19 vaccines in Nigeria: a scoping review - Ifeanyi, Chikezie; Okechukwu, Emmanuel; Tosin, Olushola; Hyacinth, Ichoku; Ataguba, John Ele-Ojo; Muriithi, Grace Njeri; Achala, Daniel Malik; Adote, Elizabeth Naa Adukwei; Mbachu, Chinyere Ojiugo; Beshah, Senait Alemayehu; Nwosu, Chijioke Osinachi; Tlhakanelo, John Thato; et al. (Frontiers in Health Services, 2025)
The coronavirus disease (COVID-19) is one of the largest public health threats in recent times, with significant health, economic, and social consequences globally. The WHO reported that over 651 million cases and 6.6 million deaths were attributed to COVID-19 globally. The Nigeria Centre for Disease Control (NCDC) in 2022 revealed that 266,057 cases with 3,155 deaths were reported. All the thirty-six states and the Federal Capital Territory (FCT) of Nigeria were affected, but Lagos and the FCT reported the highest number of cases. However, it is possible that these numbers do not accurately reflect the severity of COVID-19 disease in Nigeria because the country had only tested 5,160,280 people as at 2022, despite a population of around 200 million. Nigeria did not meet its 2021 vaccination target, prompting the need to identify the contextual factors affecting vaccine access and uptake as well as vaccine hesitancy in Nigeria and document the approaches that can be deployed to reduce opposition to vaccination as well as improve advocacy for vaccine equity. This scoping review, conducted using Arksey and O'Malley's framework, aimed to explore the factors influencing COVID-19 vaccine hesitancy and uptake in Nigeria. A comprehensive literature search was conducted across electronic databases, including Google Scholar and PubMed, with studies from Nigeria published in English. The review included 25 studies on vaccine hesitancy, uptake, and willingness to accept COVID-19 vaccination, identifying barriers at the national, community, and individual levels. The results indicated that 90% of the studies showed low vaccine acceptance and uptake, with barriers related to vaccine availability, misinformation, cultural and religious influences, socioeconomic factors, and lack of trust in the health system. Socio-demographic factors such as gender, age, education, and income were identified as key influences. The findings highlight the need for targeted, evidence-based strategies to address vaccine hesitancy, improve vaccine distribution, and engage diverse population groups to enhance vaccination uptake across Nigeria.